Edutainment in Ruang Guru Clash of Champion: A Semiotic Perspective - Ali, Ahmad Jum'a Khatib Nur; Riady, Yasir (CV. Tripe Konsultan, 2025)
This study explores Ruang Guru Clash of Champion (COC) as an edutainment phenomenon in the digital education landscape. Using a qualitative phenomenological approach, the research analyzes how COC integrates education and entertainment through the concept of edutainment. Data were collected from 15 videos published on Ruang Guru's official YouTube channel and analyzed using Saussure's theory of signification, which includes elements of the signifier and the signified. The findings indicate that COC comply to edutainment principles by presenting engaging, interactive, and competitive learning experiences. The competition is constructed as a prestigious academic event through visual elements such as a coliseum-shaped stage, medals and trophies as symbols of achievement, and alma mater jackets representing institutional identity and pride. Additionally, the role of tutors, both in digital form (Aurora) and as global mentor figures (Heo Seong Beom), streghten the image of innovative modern education. The study concludes that COC not only delivers education in an entertaining format but also shapes a new perception of academic competition as a dynamic, prestigious, and technology-driven experience. Thus, COC exemplifies how the education industry can adapt edutainment strategies to attract the digital generation.